Type-2 fuzzy sliding mode control of a four-bar mechanism - Koca, Gonca O.; Akpolat, Zuhtu H.; Özdemir, Mehmet (Acta Press, 2011)
This paper describes a new control scheme for the robust crank angular speed control of a four-bar mechanism driven by a DC motor. The proposed control method is based on type-2 fuzzy logic and sliding mode control (SMC) technique. Type-2 fuzzy control (FC) systems are characterized by type-2 membership functions which are useful in circumstances where it is difficult to determine an exact membership function. They are also very effective to handle uncertainties because type-2 fuzzy systems can model them and minimize their effects. SMC is a robust control method against parameter variations and external disturbances. Type-2 fuzzy logic and SMC can be combined to use the advantages of both methods and thus to improve the effectiveness of the controllers. One of the most important advantages of the use of SMC with type-2 FC is to reduce the number of fuzzy rules and thus to obtain a simpler and more practical control algorithm to use in real applications. To show the effectiveness of the proposed controller, simulation results of the Type-2 FC and Type-2 FSMC systems are presented in the paper.
Keywords: Four-bar linkage system; Four-bar mechanism; Sliding mode control; Type-2 fuzzy logic